Effect of nanostructured silica additives on the extrusion-based 3D concrete printing application - Liu, Zhenbang (2023)
Recently, 3D printing technology has become more popular in the field of construction. For the extrusion-based 3D concrete printing (3DCP) process, the cementitious material needs to be strong and flowable enough to ensure buildability and pumpability. Nanostructured silica, a kind of additive, has been used to modify the 3DCP concrete to meet these requests. However, most previous studies focused on the effect of nanostructured silica on rheological properties and failed to link the obtained rheological properties of nanostructured-silica-modified cementitious materials to the performance in 3D printing. In this paper, the 3DCP mixture based on premix cement, river sand, silica fume, and water was modified by different dosages of nanostructured silica (from 0.25% to 1.00% by the total weight of the 3DCP mixture). The effects of nanostructured silica on the rheological, hydration, printing, and microstructural properties were determined by rheological tests, stress growth tests, setting time tests, printing tests, and scanning electron microscopy (SEM) tests, respectively. This paper revealed that the nanostructured silica has a positive effect on 3DCP buildability but negatively affects the printing quality, which fits the effect of nanostructured silica on the rheological properties. Hence, the determined rheological properties can qualitatively evaluate the printing performance of nanostructured-silica-modified cementitious materials.